Investigating the influence of a thin copper film coated on nickel plates through physical vapor deposition for electrocatalytic nitrate reduction - Meshram, Sumit Maya Moreshwar; Gonugunta, Prasad; Taheri, Peyman; Jourdin, Ludovic; Pande, Saket (Frontiers in Materials, 2025)
The removal of nitrate (NO3−) from water and its subsequent valorization for various applications are crucial due to environmental, health, and economic considerations. A promising method for its removal is the process of electrocatalytic reduction of nitrate. Copper/nickel (Cu/Ni) composite electrodes have demonstrated potential for this process in aqueous solution, however, the effect of thin Cu film coated on Ni using physical vapor deposition (PVD) has not been investigated for NO3− removal. Here, the PVD technique was employed to deposit a thin film of Cu onto a Ni plate to form Cu-Ni composite electrodes of varying Cu thicknesses (25–100 nm), enabling the investigation of the influence of the Cu film thickness on NO3− reduction. Electrodes prepared using PVD were utilized for electrocatalytic nitrate reduction (NO3RR) for the first time. The Cu-Ni electrodes were analyzed using X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM) to examine the deposited Cu film which is critical for NO3− reduction and ammonium (NH4+) selectivity. The Cu film was found to be uniformly distributed on the Ni plate without any additional contamination. Cyclic voltammetry was performed to obtain the information on electron transfer between the Cu-Ni electrode and the nitrogen (N2) species on the surface. NO3− was primarily reduced to NH4+, with no significant difference in the NO3− conversion rate observed as a function of the Cu thickness. As the Cu thickness increased, the current density decreased. This study also investigated the effect of stirring on NO3− reduction, considering potential applications where rotation or stirring is not feasible such as in some batteries. The findings of this investigation indicate that thin film coated electrodes fabricated using the PVD method exhibit capability for NO3− elimination through electrocatalytic reduction processes.